2006
DOI: 10.1177/0954008306066540
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Behavior of Kevlar 49 Fibers: Part II. At T values < Td

Abstract: The residual effects of thermal aging of Kevlar 49 fibers in the temperature range 150-450′C have been analyzed. Thermal aging introduces crystallographic as well as macro-structural changes. Weight losses and deterioration in tensile properties were also observed. The order in which the deterioration in crystallinity, weight and tensile strength occur has been identified. Master curves for predicting the time needed for 50% deterioration at various temperatures and the corresponding activation energy have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…The TGA † of the nanotube-Kevlar composite showed the main nanotube decomposition peak and a shoulder at 450 C which corresponds to the decomposition temperature of Kevlar. 16 The peak at 300 C may is most likely associated with further decomposition of the Kevlar. There is a significant shifting downwards of the nanotube peak most likely due to the partial damage and oxidation of the nanotubes by the mixture of acids.…”
mentioning
confidence: 99%
“…The TGA † of the nanotube-Kevlar composite showed the main nanotube decomposition peak and a shoulder at 450 C which corresponds to the decomposition temperature of Kevlar. 16 The peak at 300 C may is most likely associated with further decomposition of the Kevlar. There is a significant shifting downwards of the nanotube peak most likely due to the partial damage and oxidation of the nanotubes by the mixture of acids.…”
mentioning
confidence: 99%
“…Such a relationship between mechanical properties and thermal exposure confirms that the level of damage to meta-aramid fibre is a function of both temperature and duration of thermal ageing, which is consistent with the previous results from the X-ray diffraction method and scanning electron microscopy. Iyer et al [17,18] carried out similar research on another common fabric in construction of firefighters' protective clothing, para-aramid. They correlated some features of an X-ray diffraction pattern such as position and half width of reflection peaks and integrated intensity of the diffraction profile, with the temperature and duration of exposure.…”
mentioning
confidence: 95%
“…Fire Technology 2011 Iyer et al [17,18] examined the effects of thermal exposures on para-aramid specimens. Specimens of para-aramid were aged in a series of isothermal tests in a furnace using a variety of temperatures from 150°C to 550°C (the fabric's decomposition temperature), for cumulative durations ranging from 0.5 to 7000 h in one to 12 stages.…”
mentioning
confidence: 99%
“…Rossi et al 14 showed that when the heat flux was the same, the effect of convective heat exposure on the tensile strength was greater than that of radiant heat exposure. Iyer 15 and Iyer and Yijayan 16 used scanning electron microscopy (SEM) to observe the surface of the fabric at the early stage of thermal degradation, and the phenomenon of tissue spalling was discovered on the fabric surface. In the later aging process, holes were found on the surface of the fabric, which were related to the decomposition of the material.…”
mentioning
confidence: 99%